On the Dynamics of the Damped Extensible Beam 1d-Equation - Lizama-Yanez, C (Academic Press, 2023)
We show that the solutions of the linearized damped extensible beam equation exhibit a chaotic or stable behavior that depends on the distribution of the physical parameters of the equation. Such dynamical behavior is achieved in Herzog-like spaces. Our results provide new insights into the damped extensible beam equation by finding a critical parameter whose sign determines such qualitative properties. © 2022 Elsevier Inc.
Keywords: Stability; C0-semigroups; Chaos; Damped extensible beam equation; Herzog spaces